Senam Hamil Berhubungan dengan Lama Persalinan Kala II pada Primi dan Multigravida - Wijayati, Wahyu; Asiyah, Siti; Mazidah, Yuyun (STIKES Karya Husada Kediri, 2023)
The Implementation of pregnancy exercises can contribute positively to the opening of the cervix, coordinated uterine activity during labor, and significantly found an earlier on-set of labor and a shorter duration of labor. The aim of this research was to determine the relationship between pregnancy exercise and the length of the second stage of labor in both primi and multigravida at the Polindes, Jrebeng Village, Dukun District, Gresik Regency. This research is an observational analytical study with a cross sectional approach. The population is all mothers giving birth at the Polindes, Jrebeng Village, Dukun District, Gresik Regency. From May to July 2023, there were 57 mothers giving birth. The sample size was 50 mothers giving birth. The sampling technique is purposive sampling. The research will be carried out from May to July 2023. Data collection instruments used questionnaires, observation and partographs. Data analysis used the chi-square test. The results of the study showed that there was a relationship between pregnancy exercise and the length of the second stage of labor in both primi and multigravida [Chi-Square Test results in primigravida ( count (7.3) > table (3.84)); whereas in multigravida ( count (6.31) > table (3.84))]. This can happen because the implementation of pregnancy exercises in both primi and multigravida can contribute positively to the opening of the cervix and coordinated uterine activity during labor, and significantly found an earlier on-set of labor and shorter labor duration. Conclusion: implementing pregnancy exercises can shorten the length of the second stage of labor.